Analisis Sistem Penyimpanan Logistik Sediaan Farmasi di UPT Puskesmas Padang Bulan - Mutia Friska; Listi Tri Syafira; Riska Ananda; Dhea Salshabila Br. Sitepu; Fhidiana Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The logistics storage system for pharmaceutical preparations is a crucial aspect in health service management, especially in primary care facilities such as Community Health Centers. This study aims to ensure that drug storage including spatial layout, storage methods, stock card recording, and drug quality monitoring are in accordance with the provisions so that the availability and quality of drugs are well maintained to support optimal health services at the Padang Bulan Community Health Center UPT. This study uses a qualitative research method with a case study approach to analyze the logistics storage system for pharmaceutical preparations at the Padang Bulan Community Health Center UPT. Primary data were collected through in-depth interviews with key informants consisting of pharmacists and other related staff directly involved in drug storage management. The results of this study indicate that in general the drug storage system at the Padang Bulan Community Health Center has met most of the established standards. The application of the FIFO and FEFO storage methods has also been carried out to maintain quality and prevent expired drugs. This study resulted in the analysis of the logistics storage system for pharmaceutical preparations at the Padang Bulan Community Health Center UPT referring to the Minister of Health Regulation Number 74 of 2016, concluded that in general the storage system has been running in accordance with the established standards. Storage space and supporting facilities such as shelves, special cabinets, temperature and humidity settings have met the criteria for maintaining drug quality.